An insight into the gut microbiota of healthy and allergic West Highland Whiter Terrier dogs - Vera Felten; Jonathan Louis Turck; Stefan Unterer; Claude Favrot; Jan Suchodolski; Nina Maria Fischer; Ana Rostaher (PLoS ONE, 2025)
Canine atopic dermatitis (cAD) is a multifactorial, genetically predisposed inflammatory skin disease, with a high prevalence in many different dog breeds, with certain breeds being particularly affected, like the West Highland White Terrier (WHWT). While gut microbiome alterations are linked to allergic diseases in humans and some dog breeds, this relationship has never been investigated in WHWT dogs. This study aimed to compare the gut microbiome of allergic and healthy WHWT dogs to explore its role in cAD. Fecal samples from 21 WHWT dogs (12 allergic, 9 healthy) were analyzed using DNA shotgun sequencing and qPCR assays. No significant differences were observed in alpha or beta diversity, and no significant abundance of bacterial taxa was identified between allergic and healthy dogs. The Dysbiosis Index (DI) did not differ between the allergic (median −4.2, range −6.6 to 1.3) and healthy group. However, a moderate negative correlation was found between the relative abundance of E. coli and pruritus severity. These findings indicate that while the gut microbiome overall may not significantly contribute to cAD pathogenesis in WHWT dogs, some species like E. coli may be associated with clinical symptoms. Further studies are needed to investigate this relationship and to explore the role of genetics and the gut microbiota across different breeds with a larger number of dogs and with multi-omics approaches.